2022
DOI: 10.1158/1535-7163.mct-22-0059
|View full text |Cite
|
Sign up to set email alerts
|

FGFR4-Targeted Chimeric Antigen Receptors Combined with Anti-Myeloid Polypharmacy Effectively Treat Orthotopic Rhabdomyosarcoma

Abstract: Rhabdomyosarcoma (RMS) is the most common soft tissue cancer in children. Treatment outcomes, particularly for relapsed/refractory or metastatic disease, have not improved in decades. The current lack of novel therapies and low tumor mutational burden suggest that CAR T therapy could be a promising approach to treating RMS. Previous work identified Fibroblast Growth Factor Receptor 4 (FGFR4, CD334) as being specifically upregulated in RMS, making it a candidate target for CAR-T cells. We tested the feasibility… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…and was used as a potential therapeutic target in a few in vitro studies using FGFR4-CAR-T cells. 53,54 In one preclinical study, futibatinib, a pan-FGFR inhibitor, showed growth inhibition in RMS cell lines while inhibiting phosphorylation of FGFR4 and its downstream targets. 55 However, an FGFR4 V550L-mutant cell line developed from a patient with ERMS responded to FGFR4-specific inhibitors, but not to a pan-FGFR inhibitor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and was used as a potential therapeutic target in a few in vitro studies using FGFR4-CAR-T cells. 53,54 In one preclinical study, futibatinib, a pan-FGFR inhibitor, showed growth inhibition in RMS cell lines while inhibiting phosphorylation of FGFR4 and its downstream targets. 55 However, an FGFR4 V550L-mutant cell line developed from a patient with ERMS responded to FGFR4-specific inhibitors, but not to a pan-FGFR inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…In RMS, the most common FGFR alteration occurs in FGFR4 gene, which is altered in 10% of cases, either by amplifications or mutations, and was used as a potential therapeutic target in a few in vitro studies using FGFR4‐CAR‐T cells 53,54 . In one preclinical study, futibatinib, a pan‐FGFR inhibitor, showed growth inhibition in RMS cell lines while inhibiting phosphorylation of FGFR4 and its downstream targets 55 .…”
Section: Discussionmentioning
confidence: 99%
“…The other target of interest, the Fibroblast Growth Factor Receptor 4 (FGFR4) is a receptor tyrosine kinase, that shows very specific expression in RMS, and in normal tissues is only expressed at low levels in liver and in mature skeletal tissue (41, 42, 43, 44). FGFR4-CAR T cells are active in vitro against both aRMS and eRMS cell lines (45, 46), and show effective response against disseminated disease in vivo , but not in an RMS orthotopic model (47). Interestingly, the combination of FGFR4-CAR T cells with pharmacological inhibition of the myeloid component in stroma allowed FGFR4-CAR T cells to eradicate orthotopic RMS tumors in mice (47).…”
Section: Introductionmentioning
confidence: 99%
“…FGFR4-CAR T cells are active in vitro against both aRMS and eRMS cell lines (45, 46), and show effective response against disseminated disease in vivo , but not in an RMS orthotopic model (47). Interestingly, the combination of FGFR4-CAR T cells with pharmacological inhibition of the myeloid component in stroma allowed FGFR4-CAR T cells to eradicate orthotopic RMS tumors in mice (47).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation